A study of the problems in maintenance due to design / Mohamad Haafiz Sa’adon - Sa’adon, Mohamad Haafiz (Faculty Architecture, Planninng and Surveying, 2015)
Malaysia is one of the fast growing countries as followed the vision of Wawasan 2020 which is to become a developed country with first class infrastructure (Mohamad, 1991). He also mentioned that in order to fullfil the vision, the facilities and assets were extremely rapid developed especially building construction and infrastructure due to the need of organisation and society. Every country has its own architectural feature and that is how Putrajaya was developed. For example, in Putrajaya, the design and the colour of the buildings also differ from those usually found in this country. This is due to the association of architecture behind the Putrajaya future plan. In recent years, number of high rise building is rapidly increasing in Malaysia. In addition the demand of living space and shortage of land which due to the increasing of density population also contribute to this phenomenon. As the number of building increase, the need to use the new construction materials, designs and technologies are becoming more essential. It is because; these are main consideration that should be done in a new building construction in order to become a developed country with a first class infrastructure